(untitled) (Journal of the College of Basic Education, 2025)
Resources Grammatical and morphological are very important for the teacher and the student and emphasize the importance of the book and Our approach is descriptive analytical And the importance of taking about scholar Then the scholars mentioned who are specialists in this field, then I mentioned the resources and how the scholars mentioned and the names of the books and explanations that Al-Attar used, and how he mentioned the grammatical difference between the groups of Al-Basrin, Al-Kufin, and Al-Baghdadien. After that, the methods of transmission and quotation were mentioned, and Al-Attar mentioned a lot of the Noble Qur’an in the writing and hadiths of the Prophet In addition to the speech of the Arabs, poetry and prose through direct and indirect transmission, and it is also transmitted literally or in meaning, which is the method of scholars. This is what we have received from his book. Haashiyat al-Attar (d. 1250 AH) on the explanation of al-Jalal al-Muhalli (d. 864 AH) JAM’ AL-JAWAMI al-Subki (d. 771 AH) They are among the leading scholars of Shafi’i jurisprudence, thanks God first and last